Afrosamurai : uma análise sobre a representação de um heroí e protagonista negro na narrativa transnacional do Anime - Rangel, Edson Alves (2016)
This study analyzes the representation of a black player in the transnational anime AfroSamurai. In this analysis, we demonstrate that the narrative construction of the series, built in the form of a saga hero, working some issues that are relevant to the black people amid the world of representation and science fiction of a globalized society. Issues related to the deconstruction of racial determinism formed amid modernity and reconfigured in the midst of post-modernity. And that treatment of these issues is approaching to that given by the Afrofuturism approach that works the relationship between science fiction and political issues relevant to black people. We also demonstrated that the visual narrative of the Afro Samurai series approaches another approach to modernity experience and post-modernity, from a Japanese perspective, in order to reconfigure the treatment and approach to this narrative construction gives the issues that are relevant for black people.